Tanggung Jawab Sosial, Ekonomi, dan Lingkungan PT Indocement Tunggal Prakarsa Tbk (PT ITP) melalui Program Reduce, Reuse, Recycle, dan Recovery Kantong Semen - Erna Lestianingrum; PT Indocement Tunggal Prakarsa Tbk Unit Palimanan; Teguh Ariyanto (BRIN Publishing (Penerbit BRIN), 2022)
PT Indocement Tunggal Prakarsa Tbk (PT ITP) Unit Palimanan has performed efforts to reduce, reuse, recycle, and recovery (4R) of cement bags as an attempt to utilize resources in efficient manners. In this study, the 4R program was evaluated to gain information on the impacts of the program in social, economic and environmental benefit as a part of corporate responsibility to the community and the environment. The study was conducted by analyzing data of cement bags and other non-hazardous wastes from 2016–2020, both generated and utilized in the 4R program. The evaluation results show that the reduction program of replacing 3-ply cement bags with 2-ply cement bags is dominantly able to reduce the tonnage of cement bag waste (up to 3,000 tons/year). The reuse, recycle, and recovery programs for cement bags to produce handicrafts and Refuse-Derived Fuel (RDF) was able to contribute up to 20% of the total tonnage of the 4R program. The cement bag reduction program (replacement of 3-ply paper with 2-ply) has environmental and economic benefits for the company. Reuse, recycle, and recovery programs for cement bags are able to provide wider benefits not only for the company and the environment but also for the community. The 4R program reduced emissions to an average of 1,404 tons of CO2/year, where the dominant contribution came from the reduction effort of replacing 3-ply paper with 2-ply.